PENGARUH PEMBELAJARAN AKIDAH AKHLAK TERHADAP KARAKTER TANGGUNG JAWAB PESERTA DIDIK KELAS VII DI MTS AL-I’ANAH KOSAMBI - Putri, Rahmawati; Karyawati, Lilis; Karnia, Nia (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2023)
There are still students who lack self-discipline to become the driving force behind this research. While learning is a process designed by the teacher to help students think creatively and obtain new information in order to improve mastery of subject matter. Students who model reliable behavior should acquire and expand their self-confidence as they learn moral convictions. By examining these issues, the title of this research is "The Influence of Akidah Akhlak Learning on the Character of Responsibilities of Class VII Students at Mts Al-I'anah Kosambi". This study intends to find out the truth of learning the ethics of the creed, and the personality of obligations, as well as the impact of learning the ethics of the creed on the personality of compulsory class VII students at Mts Al-I'anah Kosambi. The ex post facto method is used in this type of research, which is a type of quantitative research. This research will take place at Mts. Al-I'anah Kosambi from February to July 2023. Samples were taken from 61 children in grade seven. Random sampling method is used to choose which sample to use. For this study, a questionnaire was used as a way to gather information. The data analysis tool uses the Validity and Reliability Test and the Chi Square Product Moment formula. Price rxy 12.807 rtable 9.488 is obtained with a significant level of 5% based on the results of hypothesis testing with the Chi Square formula. As a result, Ha is recognized and Ho is discarded. Therefore, it can be concluded that the character of the responsibility of class VII students at Mts Al-I'anah Kosambi is influenced by the learning of aqidah morals.